Association between surgical treatment and in-hospital mortality in patients with infective endocarditis stratified by NYHA classification: a nationwide retrospective study in Japan. (25th November 2020) - Kiriyama, H; Kaneko, H; Kamon, T; Itoh, H; Jo, T; Fujiu, K; Daimon, M; Morita, H; Yasunaga, H; Komuro, I
Abstract: Background: Heart failure (HF) is one of the major complications of infective endocarditis (IE). The ESC guideline described that surgical treatment should be performed for the patients with IE complicated with HF. However, decision making of surgical indication in real-world clinical setting is not easy for patients with IE concomitant with HF due to complicated conditions, and the clinical benefit of surgical intervention for IE and HF is unclear. Purpose: We sought to uncover the association between surgical treatment and in-hospital mortality among the patients admitted for community-acquired IE respectively according to the severity of HF symptoms (NYHA class I to IV). Methods: We studied 3, 403 patients diagnosed as IE (mean age 65.9 years, 61.6% males) with records of baseline NYHA classification (I to IV) who survived for more than 2 days, using the Diagnosis Procedure Combination database, a nationwide inpatient database in Japan. Patients were classified into four groups: 919 patients (27.0%) in NYHA I, 1, 007 patients (29.6%) in NYHA II, 767 patients (22.5%) in NYHA III, and 710 patients (20.9%) in NYHA IV. A multivariable logistic regression model adjusted for age, gender, Barthel Index, Charlson Comorbidity Index, and usage of inotropic therapy at admission was performed to evaluate the association between the surgical treatment and in-hospital mortality. Results: Patients with higher NYHA classification were significantly older and were more likely to be female than those with lower NYHA classification. At admission, patients with higher NYHA classification had lower baseline activities and higher comorbidities, and also had more complications including stroke, shock and disseminated intravascular coagulation than those with lower NYHA classification. In-hospital mortality was seen in 406 patients (11.9%) in the entire cohort. The mortality rate significantly increased with the NYHA class (NYHA I, 3.6%; NYHA II, 8.4%; NYHA III, 11.9%; NYHA IV, 27.9%: p<0.001). According to the multivariable logistic regression analysis, surgical treatment was independently associated with lower in-hospital mortality (Odds ratio 0.395, 95% Confidence Interval 0.297–0.526; p<0.001). A fragmentated analysis in each NYHA classification showed that the survival benefit of surgical intervention was pronounced in patients with higher NYHA class (Figure). The limitation of our study was including the potential unmeasured confounders, which lead to overestimate the relationship between the surgical treatment and in-hospital mortality even after excluding the critically ill patients who died within 2 days and adjusting for the measured confounders. Conclusion: Surgical treatment was associated with lower in-hospital mortality among the patients with IE complicated with HF, particularly among those with more advanced HF status. Our study implies that surgical treatment might be beneficial for the patients with advanced HF. Funding Acknowledgement: Type of funding source: None